Influence of constructive and geometric parameters of the end cutters on the microprofile characteristics of casting surfaces - Kusyi, Yaroslav; Kuk, Andrij; Topilnytskyy, Volodymyr; Rebot, Dariya; Bojko, Mykhailo (Technology audit and production reserves, 2021)
The object of research is the technological route of machining of an aluminum alloy casting. The research carried out is based on the basic principles of functionally oriented design of technological processes in the manufacture of products. The main hypothesis of the study is the need for a systematic approach to study the effect of cutting modes of a certain method of machining on the provision of quality parameters in the technological system (machine – device – tool – workpiece). In traditional automated systems for technological preparation of production, an object-oriented principle of designing technological processes is implemented, which provides for the step-by-step implementation of interrelated stages based on a prototyping algorithm without a functional analysis of the operational characteristics of the product. The processing of functional, mating surfaces, ensuring that the product performs its service purpose, must be implemented according to the principle of function-oriented design (FODT). A characteristic feature of FOT is the technological provision of effective operational characteristics of the product in compliance with the parameters of accuracy and quality of the surface layer of the product intended by the designer. The paper deals with the influence of the structural and geometric parameters of end mills manufactured by Sandvick (Sandviken, Sweden) on the formation of microrelief parameters of an aluminum alloy casting profile during machining on a numerically controlled vertical milling center (CNC) HAAS MINIMILL (USA). An atypical option for the FOT principle of the technological route of machining the surfaces of workpieces of machine-building products has been applied. Its feature is ignoring the requirements of the manufacturer of metal-cutting tools, which is an important element of the technological system (machine – tool – device – workpiece), regarding its use for a particular machine tool at a certain technological transition of machining. The performance criteria were the height and step characteristics of the microrelief of the profile of the surface layer of the workpiece being processed. The operating conditions of machine-building products have been determined, which make it possible to establish, in case of deviation from the manufacturer’s recommendations at the stage of technological preparation of production, the rational elements of a certain technological system: a metal-cutting machine – a device – a metal-cutting tool – a workpiece and processing modes to ensure the necessary operational characteristics.